2015
DOI: 10.1074/jbc.m114.614099
|View full text |Cite
|
Sign up to set email alerts
|

Neurons and Glia Modify Receptor Protein-tyrosine Phosphatase ζ (RPTPζ)/Phosphacan with Cell-specific O-Mannosyl Glycans in the Developing Brain

Abstract: Background:The neural extracellular matrix protein RPTP/phosphacan is abnormally glycosylated in models of congenital muscular dystrophies (CMDs). Results: RPTP/phosphacan is invested with unique and cell-specific O-mannosyl carbohydrate structures. Conclusion: RPTP/phosphacan is a major substrate for O-mannosyl glycosylation, which is a pathway critical in CMDs. Significance: Abnormal glycosylation of RPTP/phosphacan is neural cell-specific and may play a role in CMDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 64 publications
1
23
0
1
Order By: Relevance
“…However, each cell type synthesizes a unique repertoire of glycan structures and glycoconjugates. For example, different antibody epitopes on different glycoforms of phosphacan label different types of cells in the developing cerebral cortex (Dwyer et al, 2015), supporting the idea that glycoform specialization may tailor protein function at the cellular level in the brain. Additional complexity arises from changes in the expression of different glycans and glycoconjugates in different brain regions and across developmental stages (Matthews et al, 2002; Morawski et al, 2012; Torii et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, each cell type synthesizes a unique repertoire of glycan structures and glycoconjugates. For example, different antibody epitopes on different glycoforms of phosphacan label different types of cells in the developing cerebral cortex (Dwyer et al, 2015), supporting the idea that glycoform specialization may tailor protein function at the cellular level in the brain. Additional complexity arises from changes in the expression of different glycans and glycoconjugates in different brain regions and across developmental stages (Matthews et al, 2002; Morawski et al, 2012; Torii et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…POMGnT1 catalyzes the elaboration of core M1 and M2 glycans on dystroglycan (Stalnaker et al, 2010) and other extracellular proteins such as phosphacan (Dwyer et al, 2012, 2015), CD-24 (Bleckmann et al, 2009) and Cadherins (Vester-Christensen et al, 2013). Interestingly loss of POMGnT1 activity affects the production of dystroglycan carrying the Large-glycan modification that is capable of functioning as an ECM receptor, suggesting a common glycosylation pathway.…”
Section: The Dystrophin Glycoprotein Complexmentioning
confidence: 99%
“…Although α-dystroglycan (α-DG) is well known to be modified with O-mannose glycans, it is a minor among O-mannosylated proteins in the mammalian brain [114]. Instead, other glycoproteins, including PTPRZ (or its secreted form called phosphacan), CD24, mainly carry O-mannose glycans, and glycomic analyses have shown that their O-mannose glycans have a β1,6-GlcNAc branch generated by GnT-IX [115][116][117]. Mgat5b-deficient mice lack most of branched O-mannose glycans in their brain [118], and additional knockout of Mgat5 leads to complete loss of this branch, indicating that β1,6-GlcNAc branching of O-mannose glycans is mediated dominantly by GnT-IX and only marginally by GnT-V. Functionally, GnT-IX-producing glycans are involved in recovery of myelin damage [119].…”
Section: Functional Overview Of Gnt-ix (Gnt-vb)mentioning
confidence: 99%
“…RPTP is expressed in 3 alternatively spliced forms RPTP-, RPTP- , and a truncated form of RPTP- with an 860 amino acid deletion (Fig 3c). Phosphacan is the proteolytically released ecto-domain of the transmembrane protein tyrosine phosphatase receptor- of neurons and glial cells [75] and is a principal CNS proteoglycan promoting neuron-glial interactions, neuronal differentiation, myelination and axonal repair. The transient nature of cell signalling by phosphorylation requires specific phosphatases for regulatory control.…”
Section: Phosphacanmentioning
confidence: 99%